Formulation of conductive inks printable on textiles for electronic applications: a review. Issue 2 (3rd April 2022) - Boumegnane, Abdelkrim; Nadi, Ayoub; Cochrane, Cedric; Boussu, François; Cherkaoui, Omar; Tahiri, Mohamed
Abstract: Printed electronics (PE) is one of the most dynamic technologies in the world. It proposes low-cost electronic network production in flexible substrates by numerous printing techniques, (screen printing, gravure, offset, flexographic, and inkjet printing), used in various industries. In PE, ink pigments are replaced by metallic particles or precursors that transmit electrical conductivity to the printed patterns such as carbon, polymers and conductive pigments. Conductive inks play an important role in printed electronics, and despite the number of conductive ink types available on the market, there are still issues to be addressed. Some of these restrictions include the use of toxic chemical reagents and solvents and complicated manufacturing protocols, which often make the industrialization of conductive inks an even more distant goal. In particular, conductive inks based on silver nanoparticles, Graphene and PEDOT:PSS are widely studied thanks to their high electrical conductivity. On the other hand, there is still work to be done to show the interest of inks based on phthalocyanine pigments, in particular copper phthalocyanine. Nevertheless, problems related to stability, dispersion and annealing temperature often limit the application of these four types of fillers. In this review, we present general information on available conductive fillers used for the formulation of conductive inks, focusing on metallic particles, carbon fillers, pigments and polymers. The influence and technical requirements of the regularly used printing techniques, as well as the post-processing treatments to achieve the targeted performance in the obtained inks have been discussed. In addition, the surface characteristics of the various types of extensible and flexible substrates used in portable electronics are described. Moreover, some types of printed flexible electronic components as well as notable applications of electronic textiles in various sectors are exhibited. Next, the major challenges for the manufacturing of printed flexible electronics and recommendations for future research are discussed in this review